Improvement of PBB's Spatial Database by Applying the Enterprise Rule - (NIM 25106019), SUNARYO
Both of PBB (Land and Building Tax) database, attribute data and spatial data, are important to support PBB administrative activities at all DGT (Directorate General Taxes) organization level. However, the importances of them are not followed by reliability of the information system management. This can be seen from the large number of invalid PBB spatial database. PBB Geographic Information System (PBB SIG) that manage PBB database has some weaknesses, particularly spatial database. The weaknesses may pose some problems related to spatial data integrity. These problems give unfavorable impact for PBB administrative activities. Some accomplishments are required to conquer the problems. This research applies enterprise rules in spatial database by compiling enterprise rules and transforms them into the DBMS (database management system) in order to improve the spatial database integrity. The methodologies of this research are analysis of existing PBB spatial database, compiling spatial database enterprise rules, transforming enterprise rules in DBMS by spatial database reengineering, implementation into Oracle DBMS, testing and analysis. According to the test results, the PBB spatial database reengineering is capable to improve PBB spatial database integrity by prevention of invalid spatial database entrance into DBMS. A large number of weaknesses of the existing database can be solved by enterprise rules application. However, a comprehensive database test in KPPBB or KPP Pratama is required to recognize its actual capability.